2014
DOI: 10.2217/fon.14.23
|View full text |Cite
|
Sign up to set email alerts
|

Cancers of the Anal Canal: Diagnosis, Treatment and Future Strategies

Abstract: Anal cancer is an uncommon cancer; however, it is rising in incidence. There is confusion regarding nomenclature and the distinction between anal canal cancer and anal margin cancer. This article discusses the modern definition, etiology and staging of anal canal and anal margin cancers. Modern chemotherapy and radiotherapy regimens are discussed, in addition to modern imaging and radiotherapy techniques. Future preventative strategies and potential novel treatments are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 105 publications
(115 reference statements)
0
25
0
Order By: Relevance
“…Viral DNA load in the anal lavage was comparable to that in the vaginal lavage, indicating possible viral shedding in the anal tract. Few studies have attempted to monitor viral infection in the anal tract (Bown et al , 2014; Liszewski et al , 2014; Wells et al , 2014). Our study demonstrated the feasibility of using anal lavage samples as a diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…Viral DNA load in the anal lavage was comparable to that in the vaginal lavage, indicating possible viral shedding in the anal tract. Few studies have attempted to monitor viral infection in the anal tract (Bown et al , 2014; Liszewski et al , 2014; Wells et al , 2014). Our study demonstrated the feasibility of using anal lavage samples as a diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 , 4 , 8 15 ] Accumulating evidence from countries in North America and Europe show that the incidence of HPV-associated oropharyngeal squamous cell carcinoma (OPSCC) and anal squamous cell carcinoma (ASCC) has increased over the past 2 to 4 decades, particularly among men. [ 6 , 7 , 9 , 10 , 12 19 ] Data on the epidemiology of HPV-associated cancers in Asia are more limited, but cancer registry-based studies in Korea and Taiwan found similar increases in HPV-related OPSCC. [ 20 , 21 ] Trends in other Asian countries, and across Asian ethnic groups, have not been previously studied.…”
Section: Introductionmentioning
confidence: 99%
“…Anal mucinous adenocarcinoma [ Figure 16 ] is a rare malignancy accounting for about 3% of anal cancers. [ 23 24 ] Squamous cell carcinoma is similarly rare, but is strongly associated with the human papillomavirus. Presentation of anal cancer is variable, but generally includes anal pain, bleeding, or itching.…”
Section: Casesmentioning
confidence: 99%